Mechanical Properties of Scrap Tire Crumbs-Clayey Soil Mixtures Determined by Laboratory Tests - ShanShan Li; Dayong Li (Advances in Materials Science and Engineering)
Some laboratory tests, such as Proctor compaction test, direct shear and cyclic direct shear tests, consolidation test, and unconfined compression test, were performed on scrap tire crumbs-clayey soil mixtures to study the mechanical properties of the mixtures. The results show that (1) the maximum dry unit weight and the corresponding optimum moisture content of the mixtures decrease rapidly with the increase of scrap tire crumbs content (CSTC), showing good potential for using the mixtures as lightweight fill material; (2) it is not possible to prepare the mixture when CSTC exceeds 30% due to the occurrence of cracks in the mixture after removing from a mould; and (3) the shear strength of mixtures approximately increases by 20% when CSTC is up to 30%, while the residual strength decreases by 15%, compared with that of pure clayey soil. During shearing, the dilation of the mixtures occurs, particularly under the condition of a high CSTC and a low vertical pressure. Besides, the compressive strength and consolidation settlement of the mixtures decrease with CSTC increasing. The results indicate that it is possible for scrap tire crumbs used to improve clayey soil, which is suitable to act as a fill material.